2015
DOI: 10.2139/ssrn.2673829
|View full text |Cite
|
Sign up to set email alerts
|

Public Relative Performance Feedback in Complex Service Systems: Improving Productivity Through the Adoption of Best Practices

Abstract: Managers of service organizations seek to improve productivity without eroding service quality. We explore whether privately versus publicly disclosing relative performance feedback (RPF) about individual workers' processing times can help achieve this goal. Using three years of patient encounter data from two emergency departments, one of which changed from privately to publicly disclosing RPF to physicians, we find an 8.6% improvement in productivity and no significant reduction in quality associated with im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 65 publications
(107 reference statements)
0
16
0
Order By: Relevance
“…If providers have available time, they provide more services to each customer to increase quality (Delasay et al, 2015;Hopp et al, 2007). Researchers have found that in practice, when workload is visibly high, workers "cut corners" (Oliva & Sterman, 2001) and work at a faster pace (KC & Terwiesch, 2012;Schultz, Juran, Boudreau, McClain, & Thomas, 1998;Shunko, Niederhoff, & Rosokha, 2017;Song, Tucker, Murrell, & Vinson, 2015), and that congestion-induced speed often comes at the expense of quality (Anderson, Golden, Jank, & Wasil, 2012;KC & Terwiesch, 2012;Kuntz, Mennicken, & Scholtes, 2014;Oliva & Sterman, 2001). Researchers have found that in practice, when workload is visibly high, workers "cut corners" (Oliva & Sterman, 2001) and work at a faster pace (KC & Terwiesch, 2012;Schultz, Juran, Boudreau, McClain, & Thomas, 1998;Shunko, Niederhoff, & Rosokha, 2017;Song, Tucker, Murrell, & Vinson, 2015), and that congestion-induced speed often comes at the expense of quality (Anderson, Golden, Jank, & Wasil, 2012;KC & Terwiesch, 2012;Kuntz, Mennicken, & Scholtes, 2014;Oliva & Sterman, 2001).…”
Section: The Impact Of Available Processing Timementioning
confidence: 99%
See 4 more Smart Citations
“…If providers have available time, they provide more services to each customer to increase quality (Delasay et al, 2015;Hopp et al, 2007). Researchers have found that in practice, when workload is visibly high, workers "cut corners" (Oliva & Sterman, 2001) and work at a faster pace (KC & Terwiesch, 2012;Schultz, Juran, Boudreau, McClain, & Thomas, 1998;Shunko, Niederhoff, & Rosokha, 2017;Song, Tucker, Murrell, & Vinson, 2015), and that congestion-induced speed often comes at the expense of quality (Anderson, Golden, Jank, & Wasil, 2012;KC & Terwiesch, 2012;Kuntz, Mennicken, & Scholtes, 2014;Oliva & Sterman, 2001). Researchers have found that in practice, when workload is visibly high, workers "cut corners" (Oliva & Sterman, 2001) and work at a faster pace (KC & Terwiesch, 2012;Schultz, Juran, Boudreau, McClain, & Thomas, 1998;Shunko, Niederhoff, & Rosokha, 2017;Song, Tucker, Murrell, & Vinson, 2015), and that congestion-induced speed often comes at the expense of quality (Anderson, Golden, Jank, & Wasil, 2012;KC & Terwiesch, 2012;Kuntz, Mennicken, & Scholtes, 2014;Oliva & Sterman, 2001).…”
Section: The Impact Of Available Processing Timementioning
confidence: 99%
“…Some physicians, whom we refer to as high reflectors, take time to reflect more, on average, before ordering tests than do low reflectors (Lundberg, 1998;Song, Tucker, Murrell, & Vinson, 2015;van Walraven et al, 1998). We also conduct a placebo test and show that these DD results are not a function of our data structure (Pierce, Snow, & McAfee, 2015;Song, Tucker, Murrell, & Vinson, 2015). Thus, we rank "average time to first test order" by attending physician, when justification is not present, and do a median split, where high (low) reflectors have higher (lower) average times to first order.…”
Section: Robustness Testsmentioning
confidence: 99%
See 3 more Smart Citations